Per capita water consumption for benchmarked South African service levels derived by means of explicit reasoning - Jacobs, HE; Crouch, ML; Ilemobade, A; Du Plessis, JL (Water S. A., 2022)
Per capita water use is commonly employed in single-parameter models to estimate water demand, especially in regions where model input parameters are limited. Research has confirmed that the serviced population and household size positively correlate with water consumption, but the per capita consumption of household members decreases with increased household size. A central issue driving this study was the lack of an up-to-date per capita household water use guideline in the South African context. This study followed a process of explicit reasoning and inference, informed by an extensive knowledge review, stakeholder input and interrogation of relevant data, to develop a novel per capita water use estimation tool. Five main parameters were included, namely: (i) level of water service provided, (ii) usage scenario, (iii) household size (people per household), (iv) geographic region, and (v) regional property value. A Microsoft Excel-based tool was developed and is supplied online as supplementary material with this publication. The litres per capita per day tool (LCD-tool) allows for robust per capita water use estimates, as a function of the above five input parameters. The Microsoft Excel LCD-tool provides benchmarks for diferent South African conditions, described by context-specific service levels. The planning and management of water supply and distribution systems could benefit from the findings of this study.